Factors Affecting the Perception of Disability: A Developmental Perspective - Babik, Iryna; Gardner, Elena S. (Frontiers in Psychology, 2021)
Perception of disability is an important construct affecting not only the well-being of individuals with disabilities, but also the moral compass of the society. Negative attitudes toward disability disempower individuals with disabilities and lead to their social exclusion and isolation. By contrast, a healthy society encourages positive attitudes toward individuals with disabilities and promotes social inclusion. The current review explored disability perception in the light of the in-group vs. out-group dichotomy, since individuals with disabilities may be perceived as a special case of out-group. We implemented a developmental approach to study perception of disability from early age into adolescence while exploring cognitive, affective, and behavioral components of children’s attitudes. Potential factors influencing perception of disability were considered at the level of society, family and school environment, and the individual. Better understanding of factors influencing the development of disability perception would allow the design of effective interventions to improve children’s attitudes toward peers with disabilities, reduce intergroup biases, and promote social inclusion. Based on previous research in social and developmental psychology, education, and anthropology, we proposed an integrative model that provides a conceptual framework for understanding the development of disability perception.